Irenaeus on the Trinity - Lashier, Jackson. (Vigiliae Christianae, Supplements, 2014)
In Irenaeus on the Trinity , Jackson Lashier provides a fresh reading of Irenaeus' understanding of God, in dialogue with his opponents and sources, which reveals a more developed Trinitarian theology than traditionally thought. Key Trinitarian themes that emerge are the Fatherhood of God, the mutual indwelling relations of Father, Son, and Spirit, and the cooperative divine work of all three in the economy. The study finds Irenaeus' thought to depart in these areas from standard second century trajectories--Apologists and Gnostics--moving Trinitarian theology in the direction of more developed Trinitarian thought of later centuries. This monograph offers not only a better understanding of Irenaeus' thought, but also a fuller picture of the development of Trinitarian thought in early Christianity.